À propos de la construction historique de la pastorale souletine - Inchauspe, Veronique (Anuario del Seminario de Filología Vasca "Julio de Urquijo", 1999)
The author has divided her work into two different parts. In the first part, "The pastoral in Zuberoa", we have reflected on the issue of the identity of gender in pastorals in Zuberoa from three points of view. These are the oblivion of pastorals from northern Navarre and Lapurdi, the search for original texts and the original myth of the first "errejent" (director) in Zuberoa. The second part, "Pastoral symphony", is a much more subjective construction. Here the author has made an effort to imagine the birth of pastoral theatre within a traditionally pastoral society. This she does in order to discover why the inhabitants of Zuberoa speak of their theatre as if they were speaking about a natural expression, which approximates us to the mountainous nature of their soul and their culture.